Deskripsi Pengaruh Kepuasan Kerja Terhadap Kinerja (PT NI, Area Marketing Jawa Barat) - Melina Hermawan; Ronald Sukwadi; Christina Christina; Derdya Maharsayani (Jurnal Pendidikan Indonesia, 2025)
This study aims to obtain an overview of the influence of job satisfaction on performance, and whether the relationship between job satisfaction and performance is strengthened by work motivation. The focus of the study on PT N I, especially the West Java marketing area, has employees with good performance, the management believes that employees are satisfied with their jobs. The performance, job satisfaction, and motivation variables are obtained based on research by Margareth Y.L. The performance variable as the dependent variable and the job satisfaction variable as the independent variable. The collection of levels of satisfaction, motivation and performance was carried out by distributing questionnaires to all employees in the West Java Marketing area as many as 25 people, and a Focus Group Discussion (FGD) was conducted with the management. The results of data processing showed a correlation coefficient of 0.873 indicating a very strong relationship between job satisfaction and performance which is influenced by work motivation. The determination coefficient value in the first regression was 23.43%, while after the second regression equation the determination coefficient value increased to 76.21%, which means that work motivation strengthens the relationship between the influence of job satisfaction on performance. Even though the results of the correlation and determination coefficients are high, the results of the F test and t test showed no significant influence between job satisfaction and performance either with or without intervening variables. These results can show that there is a relationship between satisfaction, motivation and performance, but the influence of satisfaction on performance is not significant, therefore, to improve performance, it does not mean having to improve job satisfaction.